2021
DOI: 10.24018/ejbio.2021.2.3.202
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Anopheles Mosquitoes to Deltamethrin and Bendiocarb Insecticides in Nasarawa Local Government Area, Nasarawa State Nigeria

Abstract: Anopheles mosquito’s resistance to insecticides has been one of the major challenges in eradicating malaria. This study was carried out to determine the susceptibility status of Anopheles mosquitoes to Deltamethrin and Bendiocarb in some communities of Nasarawa Local Government Area of Nasarawa State for four months. The research was carried out at the insectary laboratory of Nasarawa State University Keffi. Center for Disease Control (CDC) bioassay bottle and WHO impregnated papers were used to test the susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…However, On the other hand mosquitoes from JaroBakari, Kalshingi, Lapandintai, Popondi and Sabon Layi were susceptible to bendiocarb (0.1%) with mortality >98%. This agree with the recent study done in Nasarawa (Lama et al, 2021), Adamawa (Wahedi et al, 2021), Umudike (Ekedo and Ukpai, 2020), 100% recorded in Niger Delta zone (Ekerette and Ebere, 2022) and 100% observed in Kinshasha (Zanga et al, 2022). Possible resistance was registered in Zagaina (mortality 93%), Ajiya quarters (mortality 93%) and Lakolin (mortality 95%) respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, On the other hand mosquitoes from JaroBakari, Kalshingi, Lapandintai, Popondi and Sabon Layi were susceptible to bendiocarb (0.1%) with mortality >98%. This agree with the recent study done in Nasarawa (Lama et al, 2021), Adamawa (Wahedi et al, 2021), Umudike (Ekedo and Ukpai, 2020), 100% recorded in Niger Delta zone (Ekerette and Ebere, 2022) and 100% observed in Kinshasha (Zanga et al, 2022). Possible resistance was registered in Zagaina (mortality 93%), Ajiya quarters (mortality 93%) and Lakolin (mortality 95%) respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Over use of chemical pesticide for agricultural purposes for many year can exact huge selection pressure on the larval stages of mosquitoes which might resulted into development of insecticide resistance of the mosquito larvae (Piameu et al, 2021). Pyrethroid resistance in malaria vector was first reported in Nigeria as cited by Awolola et al (2007) in 2002 since then, several studies have reported mosquitoes developing resistance to one or more insecticide classes ( Oduala et al, 2012;Oduala et al, 2019;Fagbohun et al, 2020;Lama et al, 2021;Owolabi andAyankoya, 2023 Adeogun et al, 2023). Although, DDT (4%) was banned since the 80s due to long persist in the environment, residual efficacy on malaria vector and other vector-borne disease vectors (Jacob and Yoriyo, 2015) high level of resistant was established across all the ecological zone of Nigeria and Africa (Ibrahim et al, 2014;Habibu et al, 2017;Oduala et al, 2019;Ahmed-Yusuf et al, 2020;Adeogun et al, 2023;NDri et al, 2023) which is similar to our result from all the communities except Popondi (99%), SabonLayi (98%) where susceptibility was established and possible resistance was registered in Kalshingi (94%) and Lapandintai (93%).…”
Section: Discussionmentioning
confidence: 99%